The Construct of Emotional Support in Quranic Memorization Students: A Study on the Dynamic Influence of Reliable Relationships, Trusted Guidance, Psychological Well-being, and Quranic Memorization Achievement - M. Agung Rahmadi; Achmad Syahid; Said Agil Husin Al Munawar; Abdul Rahman Shaleh; Helsa Nasution; Luthfiah Mawar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Using a mixed-method approach, This study examines emotional support for Quranic memorization students (santri tahfidz) in Islamic boarding schools (pesantren). Quantitative analysis of 515 santri tahfidz revealed high levels of emotional support (M = 3.74, SD = 0.68) with two primary dimensions: reliable relationships (74.96%) and trusted guidance (75.17%). Multiple regression analysis uncovered a significant relationship between emotional support and Quranic memorization achievement (β = 0.42, p < .001, R² = 0.18). A meta-analysis of 28 studies (N = 3,627) confirmed a positive correlation between emotional support and students' psychological well-being (r = 0.39, 95% CI [0.34, 0.44]). MANOVA results indicated significant differences in santri tahfidz's perceptions of emotional support based on gender (Wilks' λ = .97, F(2, 512) = 7.85, p < .001, partial η² = .03) and age (Wilks' λ = .95, F(4, 1022) = 6.73, p < .001, partial η² = .03). These findings extend previous research by Hasfi (2018) and Vista (2018) by identifying the specific roles of teacher support (β = 0.31, p < .01) and peer support (β = 0.28, p < .01) in enhancing student resilience. Furthermore, this study contributes to a more comprehensive understanding of emotional support dynamics in pesantren tahfidz education, integrating Bronfenbrenner's (1979) ecological perspective and Deci and Ryan's (2000) self-determination theory. Finally in a practical context, the researcher evaluates this study has implications for the development of more structured and efficient emotional support intervention programs in tahfidz pesantren.